СТРАТЕГИИ РАЗВИТИЯ КРИТИЧЕСКОГО МЫШЛЕНИЯ ПРИ ПРОВЕДЕНИИ ЛЕКЦИЙ В ВУЗЕ - Григорьева, М.И. (SCIENCE and SOCIETY, 2025)
The article examines critical thinking strategies as a modern and effective approach in conducting lectures at higher education institutions. The theoretical foundations of this method, its advantages in the context of lectures are considered as well as the features of its implementation in the educational process.
Keywords: critical thinking; education; challenge; comprehension; reflection